Anti‐dumping Policies and International Portfolio Allocation: The View from the Global Funds. Issue 2 (28th February 2023) - Ding, Haoyuan; Li, Xiao; Ying, Jiezhou
Abstract: Anti‐dumping policies, as one of the most important nontariff measures to protect a country's economic interests, can have an impact not only on a country's trade and social welfare, but also on capital flows. Anti‐dumping measures can result in increased trade costs and alterations to exchange rate risk. This study investigates the impact of anti‐dumping sanctions on the international portfolio allocations of global funds. Antidumping policies can decrease the proportion of a fund's investment portfolio allocated to recently‐sanctioned countries. Closer trade ties between the sanctioned country and the country where a fund is domiciled exacerbate the divestiture, but stronger foreign direct investment links weaken the negative association. Some country and fund heterogeneities are also discussed. We find that more developed countries are less affected by the impact of anti‐dumping measures on equity fund allocations; liberalization of the economy and stable government could also mitigate the negative impact of anti‐dumping sanctions. High‐risk funds, such as growth funds or funds that invest in leveraged buyouts, showed the greatest response to changes in anti‐dumping regulations.